Factors affecting peak impact force during soccer headers and implications for the mitigation of head injuries - Auger, J.; Markel, J.; Pecoski, D. D.; Leiva-Molano, N.; Talavage, T. M.; Leverenz, L.; Shen, F.; Nauman, E. A. (PLOS ONE, 2020)
It has been documented that up to 22% of all soccer injuries are concussions. This is in part due to players purposely using their head to direct the ball during play. To provide a more complete understanding of head trauma in soccer athletes, this study characterized the effects of four soccer ball characteristics (size, inflation pressure, mass, velocity) on the resulting peak impact force as it relates to the potential for incurring neurophysiological changes. A total of six hundred trials were performed on size 4 and 5 soccer balls as well as a novel lightweight soccer ball. Impact force was measured with a force plate and ball velocity was determined using motion capture. These data were used, in conjunction with dimensional analysis to relate impact force to ball size, mass, velocity, and pressure. Reasonable reductions in allowable ball parameters resulted in a 19.7% decrease in peak impact force. Adjustments to ball parameters could reduce a high cumulative peak translational acceleration soccer athlete down into a previously defined safer low loading range. In addition, it was noted that water absorption by soccer balls can result in masses that substantially increase impact force and quickly surpass the NCAA weight limit for game play. Additional research is required to determine whether varying soccer ball characteristics will enable soccer players to avoid persistent neurophysiological deficits or what additional interventions may be necessary and the legal implications of these data are discussed.